Achieving sustainability through GST: a step towards economic growth. (25th May 2023) - Sachdeva, Timcy; Narula, Swati
The goods and services tax (GST), a comprehensive indirect tax imposed on goods and services implemented on July 1, 2017. The major taxation reform aimed at creating a single, unified market benefiting both corporate and the economy. The government tried to move a step towards economic growth and achieving sustainability by implementing GST. Changes in government policy create a cascading impact on economy which further impacts the stock market of the country. With little literature available on impact of GST on Indian stock market, the present study tries to bridge the gap and provide a new horizon to explore the aspects of GST implementation in India. The study examines the announcement effect of GST on the wealth of the shareholders in India. Further, the study investigates the impact of GST on different industries listed on S&P Sensex by applying event study methodology. The results suggest that GST announcement has no impact on shareholders' wealth.